Test of writing for chidren in kannada - K, Yeshoda (Journal of All India Institute of Speech and Hearing)
The present study aimed at developing a tool to assess the acquisition of writing in children studying in Kannada medium schools. The test was administered individually. The results indicated that children at 3-4 years of age have acquired writing skills. Writing skills begin to emerge at this age with copying and gradually with increase in age, writing to dictation, sentence completion etc., are acquired. The study showed that writing is not fully developed even at 7-8 years of age. It was also observed that practice, training and education could effect the writing.